Simulator sickness and its measurement with Simulator Sickness Questionnaire (SSQ) - Marcin P. Biernacki; Robert S. Kennedy; Łukasz Dziuda (Nofer Institute of Occupational Medicine, 2016)
One of the most common methods for studying the simulator sickness issue is the Simulator Sickness Questionnaire (SSQ) (Kennedy et al., 1993). Despite the undoubted popularity of the SSQ, this questionnaire has not as yet been standardized and translated, which could allow us to use it in Poland for research purposes. The aim of our article is to introduce the SSQ to Polish readers, both researchers and practitioners. In the first part of this paper, the studies using the SSQ are discussed, whereas the second part consists of the description of the SSQ test procedure and the calculation method of sample results. Med Pr 2016;67(4):545-555